Exploring Legal Understanding for Adolescents: Counseling on Adolescent Issues and Rights - Lesmana, Sri Jaya; Felina (The International Journal of Law Review and State Administration, 2024)
Adolescence is a sensitive phase in the course of life, where individuals are in the process of self-discovery and vulnerable to various external influences. This PKM is carried out in the form of legal counseling using an interactive method, which allows participants to actively participate in discussions and ask questions related to the material presented by the resource persons. The purpose of implementing this PKM is as a means of legal education and a means of providing a better understanding of the law, so that adolescents can avoid legal problems that can damage the future. Based on the PKM that has been implemented, it can be concluded that, first, participants' interest in legal counseling that was carried out showed a positive trend. Second, participants' understanding of adolescent problems and rights has increased. As for the advice given, both to participants (in this case adolescents and parents as the closest family) must have awareness and vigilance of adolescent conditions and behaviors in order to avoid external negative influences.